Inter-organismal signaling and management of the phytomicrobiome - Smith, Donald L.; Praslickova, Dana; Ilangumaran, Gayathri (Frontiers in Plant Science, 2015)
The organisms of the phytomicrobiome use signal compounds to regulate aspects of each other’s behaviour. Legumes use signals (flavonoids) to regulate rhizobial nod gene expression during establishment of the legume-rhizobia N2-fixation symbiosis. Lipochitooligosaccharides (LCOs) produced by rhizobia act as return signals to the host plant and are recognized by specific lysine motif receptor like kinases, which triggers signal cascade leading to nodulation of legume roots. LCOs also enhance plant growth, particularly when plants are stressed. Chitooligosaccharides activate plant immune responses, providing enhanced resistance against diseases. Co-inoculation of rhizobia with other plant growth promoting rhizobacteria (PGPR) can improve nodulation and crop growth. PGPR also alleviate plant stress by secreting signal compounds including phytohormones and antibiotics. Thuricin 17, a small bacteriocin produced by a phytomicrobiome member promotes plant growth. Lumichrome synthesized by soil rhizobacteria function as stress-sensing cues. Inter-organismal signaling can be used to manage/engineer the phytomicrobiome to enhance crop productivity, particularly in the facet of stress. Stressful conditions are likely to become more frequent and more severe in the plight of climate change.